Unilateral lesions of the cholinergic basal forebrain and fornix in one hemisphere and inferior temporal cortex in the opposite hemisphere produce severe learning impairments in rhesus monkeys. - Easton, A; Ridley, R; Baker, H; Gaffan, D (2002)
It has been proposed that isolation of the inferior temporal cortex and medial temporal lobe from their cholinergic afferents results in a severe anterograde amnesia. To test this hypothesis directly, seven rhesus monkeys received a unilateral immunotoxic lesion of the cholinergic cells of the basal forebrain with an ipsilesional section of the fornix. In a second surgery, inferior temporal cortex was ablated in the opposite hemisphere. All animals were severely impaired at learning visual scenes and object-reward associations. The impairment in learning scenes was correlated with cholinergic cell loss in the basal forebrain, but not with generalized tissue damage. Two monkeys served as surgical controls with saline injection in place of the immunotoxin, but all other procedures the same, and were not as severely impaired as those with immunotoxic lesions. Previous work has shown that monkeys with bilateral section of the anterior temporal stem (white matter of the temporal lobe), amygdala and fornix show a severe new learning impairment, and provide a model of human medial temporal lobe amnesia. One effect of this combined ablation is to isolate inferior temporal cortex and medial temporal lobe from their cholinergic afferents, possibly in addition to a direct disruption of the hippocampal system. The results of the present study, then, provide a novel link between the mechanisms of medial temporal lobe amnesia and Alzheimer's disease in which the cholinergic basal forebrain shows pathology. We propose that in both cases the mnemonic impairments result from isolating inferior temporal cortex and medial temporal lobe from their cholinergic afferents, possibly in addition to a direct disruption of the hippocampal system.